PARANEOPLASTIC SYNDROMES IN THE PRACTICE OF A NEUROLOGIST (CLINICAL CASES) - Bozhenko, N. L.; Bozhenko, M. I.; Кyrylyuk, S. Y.; Bozhenko , I. M.; Tyutko, A. O. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Paraneoplastic syndromes are the rare states caused by a change in the immune system's response to neoplasms. These include non-metastatic systemic effects that accompaniy malignant diseases. Diagnosis of these syndromes has some difficulties. In this article clinical cases of patients with paraneoplastic syndromes are analyzed and differential diagnosis is performed. Careful analysis of each clinical case is extremely important for the accumulation of experience, improvement of diagnostics and avoiding mistakes in the future.